Education and Assimilation of the Indigenous in the Novels Mariluán and Aves Sin Nido; [Educación y Asimilación del Indígena en Las Novelas Mariluán y Aves Sin Nido] - Hurtado-Ruiz, P (Universidad Autonoma de Baja California, 2024)
This paper analyzes the education of the indigenous in the novels Mariluán (1862) by Alberto Blest Gana and Aves sin nido (1889) by Clorinda Matto de Turner. Both works raise the problem of the indigenous for the national project and the difficulties that education entails. By reviewing the educational strategies in the works, the relationship between the novel and the civilizing process pursued by the authors is established. Both works show the failure of the attempts to civilize the indigenous world, determined by different actors that function as obstacles to the development of societies. © 2024, Universidad Autonoma de Baja California. All rights reserved.